2010
DOI: 10.1002/ab.20369
|View full text |Cite
|
Sign up to set email alerts
|

The link between sensation seeking and aggression: a meta-analytic review

Abstract: Substantial empirical evidence supports low resting heart rate (HR) as the best replicated psychophysiological correlate of aggression [Ortiz and Raine, 2004]; however, researchers continue to debate the explanatory mechanisms of the phenomenon. Sensation seeking has been proposed as a possible outcome of low resting HR that may lead to aggressive tendencies but findings have been inconsistent in terms of showing a relationship between sensation seeking and aggression. A meta-analysis was conducted on 43 indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 68 publications
3
58
2
4
Order By: Relevance
“…Although relations between aggressive behavior and poor impulse control and sensation seeking have been reported previously (Monahan et al, 2009;Wilson & Scarpa, 2011), we did not observe a synergistic interaction between these traits. There may be two reasons why we did not observe this result.…”
Section: Discussioncontrasting
confidence: 64%
“…Although relations between aggressive behavior and poor impulse control and sensation seeking have been reported previously (Monahan et al, 2009;Wilson & Scarpa, 2011), we did not observe a synergistic interaction between these traits. There may be two reasons why we did not observe this result.…”
Section: Discussioncontrasting
confidence: 64%
“…The participants had to be an undergraduate or graduate student because Wilson and Scarpa (2011) found that the effect size representing the relationship between sensation seeking and aggression tends to be of greater magnitude in young adult populations and therefore the proposed study used college students as participants in an attempt to increase statistical power.…”
Section: Methodsmentioning
confidence: 99%
“…The relationships between resting HR and aggression (e.g., Lorber, 2004;Ortiz & Raine, 2004), and sensation seeking and aggression (e.g., Wilson & Scarpa, 2011) have been well established. For example, a recent meta-analysis found that sensation seeking and aggression are significantly positively related, albeit with a small effect size (d ¼ .19, Wilson & Scarpa, 2011). Furthermore, a few previous studies have found that baseline HR and sensation seeking are significantly inversely related (e.g., De Pascalis, Valerio, Santoro, & Cacace, 2007).…”
Section: Sensation Seekingmentioning
confidence: 99%
“…Like LH behaviours discussed earlier, many "impulsivity" traits also show consistent sex differences. Sensation seeking (Cross, et al, 2011;Wilson & Scarpa, 2010), dysfunctional impulsivity (Cross et al, 2011) and risk taking measures (Byrnes, Miller & Schafer, 1999) indicate that men engage in more thrill seeking activities and take more risks than women. This suggests that sex differences in LH tempo may therefore be associated with sex differences in "impulsivity" traits.…”
Section: Life History and Impulsivitymentioning
confidence: 99%